Nature of LNG Arbitrage, and an Analysis of the Main Barriers for the Growth of Global LNG Arbitrage Market - Zhuravleva, P (2009)
LNG projects are highly capital-intensive and in order to protect the investment’s return, the project developers traditionally covered all their future LNG production with sales and purchase agreements (SPAs). SPAs enabled them to share the risks – LNG sellers bore price risk, while the volume risk was transferred to the buyers. Long-term contracts are still central to the LNG trade/industry, but some significant change has taken place in recent years: the elimination from some new contracts of the destination clause which was standard in long-term contracts signed before 2006, and an increase in the number of uncommitted LNG ships. LNG shipping is a crucial part of the LNG trade and just a few years ago there were a limited number of vessels that were not committed to a particular SPA with a defined delivery route.